New possibilities of the prevention and treatment of cardiovascular pathologies. the potential of molecular hydrogen in the reduction of oxidative stress and its consequences - Slezák, J; Ravingerová, T; Kura, B (Physiological research, 2024)
Disproportion between reactive oxygen species (ROS) production and the body's antioxidant system can cause oxidative stress, which is considered a common denominator in various pathological conditions, including cardiovascular diseases, aging, and cognitive disorders. The generation of free radicals, which occurs through partial reduction of oxygen, can quickly overwhelm the endogenous antioxidant system capacity of the cell. This causes lipid, protein, DNA and RNA damage, inflammation, and overall cell degeneration, which can be mitigated by various antioxidants. However, their use in human medicine did not bring the expected effect. Molecular hydrogen (H2), due to its unique physical and chemical properties, provides a number of benefits for alleviating oxidative stress. H2 is superior to conventional antioxidants as it can selectively reduce (.)OH radicals while preserving important ROS that are otherwise used for normal cell signaling. Key words Oxidative stress, Cardiovascular diseases, Molecular hydrogen, ROS, Inflammation.
Keywords: oxidační stres; Reactive Oxygen Species; antioxidancia; reaktivní formy kyslíku; kardiovaskulární nemoci; Cardiovascular Diseases; Animals; lidé; Oxidative Stress; vodík; Hydrogen; Antioxidants; Humans; zvířata